PERLINDUNGAN HUKUM HAK KEKAYAAN INTELEKTUAL ATAS DESAIN MOTIF BAGI PENGRAJIN BATIK TULIS (STUDI KASUS HAK CIPTA PENGRAJIN BATIK TULIS MADURA) - Sultoni, Yahya (FKIP Universitas Wisnuwardhana, 2018)
This paper discusses the legal protection of intellectual property rights for motif designs of Maduranese handmade batik. This is based on the diversity of the ethnic groups and the different culture of the Indonesian people. To bring out the cultural characteristics of each region, the community makes a product that aims to introduce their area to other communities. Usually, these products consist of handicrafts, processed products, agricultural products, songs, or can be works of art such as dances, etc. One of the products of cultural wealth that is the pride and identity of the Indonesian nation is batik. Batik has become a national product that is very proud of the Indonesian people and even very well known abroad. The United Nations Educational, Scientific and Cultural Organization (UNESCO) has officially given recognition and awards, so Indonesian batik is worthy of obtaining legal protection for the works produced by batik artisans. It is unfortunate if batik artisans do not know about the protection of batik designs that have been produced, the majority of them also do not know about intellectual property rights. Therefore, this paper will discuss the relations of intellectual property rights with the traditions of the Indonesian people, the mechanism of protection of traditional people's work, especially batik, and find solutions to protect the craft.Keywords: legal protection, intellectual property rights, motif designs, handmade batik